Pengembangan Potensi Wilayah Kawasan Perbatasan Negara Indonesia (Studi Kasus: Ranai-Natuna) - Eka Purna Yudha; Resa Ana Dina (Diponegoro University, 2020)
Management of national borders has become one of the main agenda of the government. The government has the priority to develop Indonesia from the periphery by strengthening regions and villages within the framework of a unitary state. The threat of national sovereignty and security disturbances at the border becomes a crucial national issue. The purpose of this study is to design the development of potential areas owned by Natuna Regency. Based on the results of the location quotient analysis, the base sectors in Natuna Regency are the Agriculture, Forestry, and Fisheries sectors. The results of the Shift-Share analysis, there are five leading sectors, namely 1) Mining and Quarrying; 2) Processing Industry; 3) Construction; 4) Wholesale and Retail Trade, and Repair of Cars and Motorcycles; and 5) Government Administration, Defense and Mandatory Social Security. Based on the results of the Inverse Distance Weighted analysis, the pattern of regional development focuses on four growth poles locations, namely Ranai, Kelarik, Strait, Midai, and Serasan. As a district with a special military zone, the development of the Natuna Regency requires synchronization between the potential of the region's natural resources, the regional government, the national army, the private sector and the community.